Oestrogens and skin – slowdown of skin aging - Wojas-Pelc, Anna; Nastałek, Magdalena; Sułowicz, Joanna (Menopause Review/Przegląd Menopauzalny, 2008)
Skin aging due to the passage of time and influence of many external (ultraviolet radiation, tobacco smoke, diet, stress) and internal (hypoestrogenism, lack of hypothalamus hormones) factors handicaps many skin functions. Disturbances of hormone management are important and well known agents responsible for skin aging. Particularly emphasized is the role of oestrogens, whose concentration becomes low during the menopausal period, causing intensification of skin aging. A distinct mechanism of induction of production of collagen via oestrogens is not known. There is a possibility of an influence on TGF-b (transforming growth factor beta), which stimulates fibroblasts to produce collagen. The data of many studies confirm the beneficial influence of exogenous oestrogens on the epidermis by decreasing transepidermal water loss, enhancing moisturizing abilities and surface lipid levels, improving skin function as a barrier and preventing dryness. Most studies give weight to the protective impact of hormone replacement therapy (HRT) on skin aging. Many studies have testified to good effects not only on collagen but also on skin elasticity and functions of some skin adnexa. However, a hazard connected with HRT in women with additional predisposing factors to development of diseases with a proven association with this therapy rule out the extension of use of HRT to improve skin functions and appearance.